Bank capital, lending booms, and busts: Evidence from Spain over the last 150 years - Mikel Bedayo; Ángel Estrada; Jesús Saurina (Latin American Journal of Central Banking (LAJCB), 2020)
In this paper, we analyze the role bank capital played in systemic banking crises and in lending expansion and contraction for nearly 150 years in Spain. We first build a measure of capital ratio (i.e., the capital to assets ratio) for Spain's banking sector, starting in 1880. Then, we analyze if more capital reduces the probability of a banking crisis using a narrative identification of banking crises in Spain. Afterwards, we run a proper econometric test to analyze bank capital levels' impact on lending cycles, controlling for other determinants of credit growth. We find robust empirical evidence that higher levels of capital reduce the probability of a crisis and that increasing the bank capital before loan expansions reduces credit growth and reduces the credit's decline if a systemic crisis materializes. Conversely, overly depleted bank capital when entering a credit contraction period severely impacts lending (i.e., may bring about a deep credit crunch), with negative and lasting effects on the economy and on society's wellbeing as a whole. The paper is particularly useful for supporting the credit cycle smoothing role of recently implemented macroprudential policies (countercyclical capital buffer).
Keywords: G01; G21; N23; N24; 330; Bank crisis; Capital ratio; Lending cycles; Leverage ratio; Macroprudential tools